Association Between Enterovirus Infection and Type 1 Diabetes Risk: A Meta-Analysis of 38 Case-Control Studies - Wang, Kan; Ye, Fei; Chen, Yong; Xu, Jianxin; Zhao, Yufang; Wang, Yeping; Lan, Tian (Frontiers in Endocrinology, 2021)
Objective The association between enterovirus infection and type 1 diabetes (T1D) is controversial, and this meta-analysis aimed to explore the correlation. Methods PubMed, Embase, Web of Science, and Cochrane Database were searched from inception to April 2020. Studies were included if they could provide sufficient information to calculate odds ratios and 95% confidence intervals. All analyses were performed using STATA 15.1. Results Thirty-eight studies, encompassing 5921 subjects (2841 T1D patients and 3080 controls), were included. The pooled analysis showed that enterovirus infection was associated with T1D (P < 0.001). Enterovirus infection was correlated with T1D in the European (P < 0.001), African (P = 0.002), Asian (P = 0.001), Australian (P = 0.011), and Latin American (P = 0.002) populations, but no conclusion could be reached for North America. The association between enterovirus infection and T1D was detected in blood and tissue samples (both P < 0.001); no association was found in stool samples. Conclusion Our findings suggest that enterovirus infection is associated with T1D.